Assessing the Sampling Quality of a Low-Tech Low-Budget Volume-Based Rainfall Sampler for Stable Isotope Analysis - Fischer, Benjamin M. C.; Aemisegger, Franziska; Graf, Pascal; Sodemann, Harald; Seibert, Jan (Frontiers in Earth Science, 2019)
To better understand the small-scale variability of rainfall and its isotopic composition it is advantageous to utilize rain samplers which are at the same time low-cost, low-tech, robust, and precise with respect to the collected rainwater isotopic composition. We assessed whether a self-built version of the Kennedy sampler is able to collect rainwater consistently without mixing with antecedent collected water. We called the self-built sampler made from honey jars and silicon tubing the Zurich sequential sampler. Two laboratory experiments show that high rainfall intensities can be sampled and that the volume of water in a water sample originating from a different bottle was generally less than 1 ml. Rainwater was collected in 5mm increments for stable isotope analysis using three (year 2011) and five (years 2015 and 2016) rain samplers in Zurich (Switzerland) during eleven rainfall events. The standard deviation of the total rainfall amounts between the different rain gauges was <1%. The standard deviation of 18O and 2H among the different sequential sampler bottles filled at the same time was generally <0.3‰ for 18O and <2‰ for 2H (8 out of 11 events). Larger standard deviations could be explained by leaking bottle(s) with subsequent mixing of water with different isotopic composition of at least one out of the five samplers. Our assessment shows that low-cost, low-tech rain samplers, when well maintained, can be used to collect sequential samples of rainfall for stable isotope analysis and are therefore suitable to study the spatio-temporal variability of the isotopic composition of rainfall.